Girl, 1983 - Ullmann, Linn, 1966- (W. W. Norton & Company, 2025)
Paris, a winter's night in 1983. She is sixteen years old, lost in unfamiliar streets. On a scrap of paper in her pocket is the address of a photographer, K, thirty years her senior. Almost four decades later, as her life and the world around her begins to unravel, the grown woman seeks to comprehend the young girl of before."--Provided by publisher